Effect of Structured Exercise-Based Intervention on Upper Quadrant Dysfunction among Fish Processing Workers with Work-Related Musculoskeletal Disorders - Gundmi V Rajesh N.; Somu Gangahanumaiah; Arun G. Maiya; Vasudeva Guddattu (Wolters Kluwer Medknow Publications, 2024)
Background: Musculoskeletal disorders (MSDs) are one of the major causes of morbidity, which affect particularly the upper quadrant in industrial settings and so upset the quality of life (QoL). The influence of the protocol of exercise-based programs at the workplace on the well-being of the worker is contradictory. The objective of the study was to find the effect of the structured exercise-based intervention on upper quadrant dysfunction among fish processing workers with work-related MSDs. Methods: The intervention group (n = 91) participated in an individually tailored structured exercise-based intervention (SEBI) program for three months, which consisted of stretching, strengthening, and active exercises. The control group (n = 93) was instructed to continue routine daily activities. The outcome measures of the cluster-randomized controlled trial were Neck Disability Index (NDI), Disabilities of Arm, Shoulder, and Hand (DASH), Visual Analog Scale (VAS), and Short Form-36, used to evaluate at baseline, eighth, and twelfth week. The data were analyzed by repeated analysis of variance and Student's t-tests. Results: The results for the overall perception of upper quadrant dysfunction showed statistically significant differences (P < 0.0001) for NDI, DASH, and VAS. Further, we obtained a significant difference in QoL between the intervention and control groups for physical and psychological health sub-domains. Conclusion: SEBI effectively enhanced the general health of fish processing workers by showing improvements in the measures of NDI, DASH, VAS, and QoL. Hence, SEBI can be recommended in the fish processing industries to achieve potential impact on upper quadrant dysfunction and improve the QoL.